2022
DOI: 10.1111/tbed.14617
|View full text |Cite
|
Sign up to set email alerts
|

High genetic diversity of Babesia canis (Piana & Galli‐Valerio, 1895) in a recent local outbreak in Berlin/ Brandenburg, Germany

Abstract: Canine babesiosis caused by Babesia canis (Piana & Galli-Valerio, 1895) is emerging in new regions in Europe since its vector Dermacentor reticulatus (Fabricius, 1794) is expanding its geographic range. In the Berlin/Brandenburg area in northeast Germany, D. reticulatus is highly abundant but in the past only one autochthonous B. canis infection was reported. Since 2015, autochthonous cases were occasionally diagnosed but numbers increased since autumn 2019. The aim of the study was to genotype autochthono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Polymerase chain reaction testing for detection of the 18S rRNA gene of piroplasm was positive in all dogs, and sequencing showed 99.47 to 100% identity with other sequences of B. canis from GenBank (Accession number ON152329‐ON152375). 16 Seventeen different genotypes were identified, with all cases from 2015 attributable to a single genotype.…”
Section: Resultsmentioning
confidence: 99%
“…Polymerase chain reaction testing for detection of the 18S rRNA gene of piroplasm was positive in all dogs, and sequencing showed 99.47 to 100% identity with other sequences of B. canis from GenBank (Accession number ON152329‐ON152375). 16 Seventeen different genotypes were identified, with all cases from 2015 attributable to a single genotype.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to D. marginatus, D. reticulatus was collected throughout the winter months (December to February), confirming winter activity of this tick species. The seasonal pattern of D. reticulatus activity in Germany is paralleled by the occurrence of autochthonous canine babesiosis cases, which have become particularly frequent as of 2019 ( 12 , 13 ), emphasizing the need of year-round tick-protection.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies on increasing endemisation of Babesia canis , e.g., by pathogen screening in Dermacentor ticks, are highly desirable, as are studies to unravel the role of D. reticulatus as a driver of TBEV spread in Germany. Given the currently reported increasing numbers of autochthonous canine babesiosis cases ( 12 , 13 ) in conjunction with the nationwide D. reticulatus occurrence and its activity during winter or the colder months, which complements that of Ixodes ricinus , a year-round tick protection of especially dogs all over Germany is strongly recommended. Furthermore, dogs entering Germany should be screened for B. canis infection to prevent establishment of further transmission foci due to importation of the pathogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. canis genotypes 18S rRNA-A (GA nucleotides) and 18S rRNA-B (AG nucleotides) occur in European countries at different rates of prevalence [ 17 , 26 ]. In the previous studies conducted in Lithuania, the 18S rRNA-A genotype was identified in 50% and 34.2% of B. canis sequences originating from D. reticulatus ticks and dogs, respectively [ 7 , 15 ].…”
Section: Discussionmentioning
confidence: 99%